THE INFLUENCE OF GREEN ZONE OFFICES TO THE GOVERNMENT ECOMONY - Sobirova Elgiza Alibek kizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
This article explains how government economies are affected by green zone offices, emphasizing how these offices may advance sustainable practices, draw in investment, and improve public health. Green zones encourage the public and business communities to support sustainable projects by acting as role models for environmentally friendly infrastructure. These zones can boost regional economies and encourage the development of jobs by establishing appealing settings for investment. The nature can easily influence to a working mood and feeling power of environment but not pressure of office is a brilliant atmospherefor people who is in any ages . Furthermore, green areas raise property prices, lower healthcare expenses, and enhance public health, all of which benefit local governments’ tax collections. The essay focuses on how green zones improve community involvement while simultaneously elevating governments to the status of world leaders in sustainability and influencing foreign policy. In the end, governments have a great chance to promote economic development and solve serious environmental issues by creating green zone offices.